1995
DOI: 10.1002/jlb.57.3.379
|View full text |Cite
|
Sign up to set email alerts
|

Secreted glucocorticoids regulate leukocyte-endothelial interactions in inflammation. A direct vital microscopic study

Abstract: Leukocytes come into intimate contact with the venular endothelium as they extravasate from blood to the interstitium during inflammation. In exteriorized tissues, the number of leukocytes rolling along the vessel wall was markedly increased in adrenalectomized and metyrapone-treated animals, relative to sham-operated and normal animals. During the development of an acute, local inflammatory response, rollers were numerically decreased and a stronger adhesion of the cells to the endothelium, with a concomitant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
13

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(59 citation statements)
references
References 35 publications
1
45
0
13
Order By: Relevance
“…Recent work suggests that glucocorticoid-induced inhibition of neutrophil accumulation is mediated by an effect on the initial steps of the process (10). Therefore, it has been suggested that glucocorticoid-induced shedding of L-selectin may be one mechanism by which glucocorticoids inhibit neutrophil accumulation in vivo.…”
mentioning
confidence: 99%
“…Recent work suggests that glucocorticoid-induced inhibition of neutrophil accumulation is mediated by an effect on the initial steps of the process (10). Therefore, it has been suggested that glucocorticoid-induced shedding of L-selectin may be one mechanism by which glucocorticoids inhibit neutrophil accumulation in vivo.…”
mentioning
confidence: 99%
“…aspirin and diclofenac. They inhibit prostaglandin synthesis (Vane, 2000) and steroids that target migration and ultimately degranulation of leukocytes (Farsky et al, 1995). In this study, the edema was obliterated by prior administration of 15 mg of diclofenac sodium 30 minutes prior to injection with formalin.…”
Section: Discussionmentioning
confidence: 69%
“…Esta resposta via Th2 é 33 mediada pela produção de EROs e citocinas como: IL-4, IL-5 e IL-13. As alterações que caracterizam a asma alérgica são: elevada IgE sérica, intensa secreção de muco, eosinofilia e exacerbada reatividade brônquica (MATTES et al, 2002;HYLKEMA et al, 2002;CAREAU et al, 2002 (ALI et al, 1999;FRANGOGIANNIS et al, 2001;KUBES, 2002 (DAHLEN et al, 1981;FORTES et al, 1991;FARSKY et al, 1995FARSKY et al, , 2004.…”
Section: Hidroquinonaunclassified
“…These leukocytes moved sufficiently slowly to be individually visible and were counted as they rolled past a selected point on one side of the vessel. The number of leukocytes adhering to the endothelium (stopped at the vessel wall) was determined at the same vascular segment (Dahlen et al, 1981;Fortes et al, 1991;Farsky et al, 1995Farsky et al, , 2004.…”
Section: Leukocyte-endothelial Interactionmentioning
confidence: 99%